Nutritional status and socioeconomic change among Toba and Wichí populations of the Argentinean Chaco - Valeggia, Claudia Rita (2010)
The prevalence of overweight and obesity is growing at an accelerated pace in disadvantaged populations. Indigenous populations all over the world, whose lifestyle is changing rapidly and drastically, seem to be particularly prone to show an increased prevalence of overweight and its co-morbidities among adults. The aim of this study was to evaluate the association between socioeconomic and nutritional statuses in adults of two indigenous populations of the Argentine Gran Chaco: the Toba and Wichí of the province of Formosa. Originally hunter-gatherers, they are now more settled and engage in temporary wage labor and local political positions. A total of 541 adults (>20 years old) participated in the study. Almost 50% of the adult Toba and 34% of the adult Wichí were overweight and 10% of adults in both populations were obese. Socioeconomic status was positively associated with body mass index in both populations. Furthermore, political connectedness with the non-indigenous sector, as in the case of community leaders, was highly correlated with obesity. Differences within and between groups can be explained by biocultural factors that include gender, diet (foraged vs store-bought), lifestyle (sedentary vs more active), and history of political power. Our study highlights the interactions among social, cultural, and political economic variables, such as political hierarchies within the group or degree of social connectedness with community leaders. By making these variables an integral part of our analysis and interpretation, we hope to improve our understanding of the situation of indigenous populations in transition. © 2009 Elsevier B.V. All rights reserved.